Enhancing Mathematics Achievement through Motivational Techniques in Community-Based Schools: A Case Study - G.C., Laxmi (Educational Journal, 2024)
This underperformance, which stems from a lack of motivation among learners, is worsened by delays in their engagement and overall academic progress in mathematics. The problem addressed in this study is the consistently low mathematics achievement among students in community-based schools, despite various educational interventions. This case study examines the motivational techniques utilized by mathematics teachers at Birendra Secondary School, a community-based school in Nuwakot, Nepal. Through qualitative methods, including classroom observations, interviews, and open-ended questionnaires, the study investigates how these strategies influence student achievement in mathematics. The Findings reveal that employing modern teaching approaches, positive reinforcement, humour, inadequate infrastructure, and strong teacher-student relationships significantly enhance students’ motivation and performance. Despite challenges such limited parental involvement, the school demonstrates commendable efforts in fostering a supportive learning environment. This research contribution offers insights into the role of motivation in enhancing mathematics education within these settings, providing recommendations for policy and practice.